2019
DOI: 10.1103/physrevapplied.12.064043
|View full text |Cite
|
Sign up to set email alerts
|

Laser-seeding Attack in Quantum Key Distribution

Abstract: Quantum key distribution (QKD) based on the laws of quantum physics allows the secure distribution of secret keys over an insecure channel. Unfortunately, imperfect implementations of QKD compromise its information-theoretical security. Measurement-device-independent quantum key distribution (MDI-QKD) is a promising approach to remove all side channels from the measurement unit, which is regarded as the "Achilles' heel" of QKD. An essential assumption in MDI-QKD is however that the sources are trusted. Here we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 82 publications
0
46
0
Order By: Relevance
“…Light coming from the wrong direction in the normal QKD optical channel can also alter the intended operation of the system. For instance, external laser light can alter the photon sources in QKD devices and has been shown to weaken security either by seeding the source laser so that consecutive pulses are not phase-independent [ 75 ], altering the wavelength to identify the state choice [ 76 , 77 ], increasing the mean photon number [ 23 , 60 , 77 ], or performing laser machining to physically alter the components inside the QKD setup [ 26 , 61 ]. In this paper, we have focused on light entering from unsuspected places, such as ventilation openings.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light coming from the wrong direction in the normal QKD optical channel can also alter the intended operation of the system. For instance, external laser light can alter the photon sources in QKD devices and has been shown to weaken security either by seeding the source laser so that consecutive pulses are not phase-independent [ 75 ], altering the wavelength to identify the state choice [ 76 , 77 ], increasing the mean photon number [ 23 , 60 , 77 ], or performing laser machining to physically alter the components inside the QKD setup [ 26 , 61 ]. In this paper, we have focused on light entering from unsuspected places, such as ventilation openings.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…However a system using BB84 for long-distance transmission might also be vulnerable to light injection attacks. It has been shown that even a small unexpected increase of the output mean photon number may break the security of decoy-state BB84 and measurement-device-independent QKD protocols [60], which are often used at longer distances. While the known combined photon-number-splitting and cloning attacks [58] require a quantum memory, the difference between the assumed and the actual key rates opens a loophole in the security of the system and must be fixed.…”
Section: Plos Onementioning
confidence: 99%
“…Our results show that the channel excess noise may be underestimated by Alice and Bob under the effects of decreased optical attenuation. Subsequently, the secret key rate is overestimated by Alice and Bob, which is coincident with the security analysis arXiv:1904.08777v1 [quant-ph] 17 Apr 2019 result of DVQKD under the effects of reduced optical attenuation [35]. Thus, the decrease of optical attenuation may open a security loophole for Eve to successfully hide her attacks, such as the classical non-Gaussian attack, i.e., the interceptresend attack.…”
Section: Introductionmentioning
confidence: 71%
“…In case of four laser setting, the wavelength control using external laser Lee et al (2017) is successfully implemented, which can be circumvented using a circulator to stop Eve from sending strong beam to the sources. Independently, single laser settings are also attacked using laser seeding and injection locking Huang et al (2019) but circulator will work against these attacks as well. Further, encoding devices can also be attacked using Trojan-horse pulses, which back-reflect from various optical elements revealing information of the sender Gisin et al (2006).…”
Section: Tablementioning
confidence: 99%